2000
DOI: 10.1034/j.1399-6576.2000.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Day‐case laparoscopy: a comparison of prophylactic opioid, NSAID or local anesthesia for postoperative analgesia

Abstract: Tenoxicam 20 mg i.v. was found to be ineffective whereas bupivacaine was superior to other groups in reducing pain and analgesic requirements. Bupivacaine also increased time to first analgesics and obtained better recovery characteristics, underlining its value in prophylactic pain management compared to the other two agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…In one study, postoperative meperidine use was decreased in patients who had preemptive bupivacaine and peritoneal lidocaine, as compared with those who had placebo [3]. Salman et al [9] found that 70% of patients treated with preemptive bupivacaine did not require postoperative narcotics, as compared to 30% treated with placebo. Partridge and Stabite [7] demonstrated that patients receiving bupivacaine in®ltration received 30% less postoperative narcotic than those receiving placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, postoperative meperidine use was decreased in patients who had preemptive bupivacaine and peritoneal lidocaine, as compared with those who had placebo [3]. Salman et al [9] found that 70% of patients treated with preemptive bupivacaine did not require postoperative narcotics, as compared to 30% treated with placebo. Partridge and Stabite [7] demonstrated that patients receiving bupivacaine in®ltration received 30% less postoperative narcotic than those receiving placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the ecacy of preemptive bupivicaine in laparoscopic surgery. After laparoscopic procedures, preincisional bupivacaine in®ltration reduces postoperative pain and analgesic requirements [9], increases the length of time to the ®rst postoperative analgesic dose [4], and decreases the length of stay in the postanesthesia care unit [7].…”
mentioning
confidence: 99%
“…Les avantages moins é vidents et qui demandent à être prouvé s sont la diminution de la douleur postopé ratoire et indirectement une convalescence plus brè ve. En effet, la diminution de la douleur parié tale par injection locale d'anesthé siques locaux amé liore les suites opé ratoires et notamment la reprise du transit digestif [15,16]. Il semble donc raisonnable d'é voquer les mêmes avantages si le nombre de trocarts parié taux est diminué .…”
Section: Discussionunclassified
“…La diminution de la douleur postopératoire est probablement un avantage et par conséquent une convalescence plus brève. En effet, la diminution de la douleur pariétale par injection locale d'anesthésiques locaux améliore les suites opéra-toires et notamment la reprise du transit digestif [22,23]. Il semble donc raisonnable d'évoquer les mêmes avantages si le nombre de trocarts pariétaux est diminué.…”
Section: Discussionunclassified